ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA MTS PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL - Desi Novianti; Wahyu Hidayat (IKIP Siliwangi, 2020)
This study aims to analyze the level of ability and difficulty of students in creative thinking with indicators of fluency, flexibility, originality and elaboration in class IX students of MTs Cimahi, which amounted to 31 students with a qualitative descriptive research method. The data analysis was obtained using the percentage formula with the SMI which was determined from the scoring rubric and the criteria for completeness of the creative thinking ability and then interpreted it into several categories with four descriptive questions as a test instrument on the SPLDV material. The results of this study indicate that most of the students' creative thinking skills have criteria that are quite creative, as many as 16 out of 31 students who already have creative abilities. The highest indicator is the indicator of fluency and flexibility, while the lowest indicator is the indicator of elaboration.